Global burden of disease of HIV-associated cryptococcal meningitis: an updated analysis. Issue 8 (August 2017) - Rajasingham, Radha; Smith, Rachel M; Park, Benjamin J; Jarvis, Joseph N; Govender, Nelesh P; Chiller, Tom M; Denning, David W; Loyse, Angela; Boulware, David R
Summary: Background: Cryptococcus is the most common cause of meningitis in adults living with HIV in sub-Saharan Africa. Global burden estimates are crucial to guide prevention strategies and to determine treatment needs, and we aimed to provide an updated estimate of global incidence of HIV-associated cryptococcal disease. Methods: We used 2014 Joint UN Programme on HIV and AIDS estimates of adults (aged >15 years) with HIV and antiretroviral therapy (ART) coverage. Estimates of CD4 less than 100 cells per μL, virological failure incidence, and loss to follow-up were from published multinational cohorts in low-income and middle-income countries. We calculated those at risk for cryptococcal infection, specifically those with CD4 less than 100 cells/μL not on ART, and those with CD4 less than 100 cells per μL on ART but lost to follow-up or with virological failure. Cryptococcal antigenaemia prevalence by country was derived from 46 studies globally. Based on cryptococcal antigenaemia prevalence in each country and region, we estimated the annual numbers of people who are developing and dying from cryptococcal meningitis. Findings: We estimated an average global cryptococcal antigenaemia prevalence of 6·0% (95% CI 5·8–6·2) among people with a CD4 cell count of less than 100 cells per μL, with 278 000 (95% CI 195 500–340 600) people positive for cryptococcal antigen globally and 223 100 (95% CI 150 600–282 400) incident cases of cryptococcal meningitis globally in 2014. Sub-Saharan Africa accounted for 73% of the estimated cryptococcal meningitis cases in 2014 (162 500 cases [95% CI 113 600–193 900]). Annual global deaths from cryptococcal meningitis were estimated at 181 100 (95% CI 119 400–234 300), with 135 900 (75%; [95% CI 93 900–163 900]) deaths in sub-Saharan Africa. Globally, cryptococcal meningitis was responsible for 15% of AIDS-related deaths (95% CI 10–19). Interpretation: Our analysis highlights the substantial ongoing burden of HIV-associated cryptococcal disease, primarily in sub-Saharan Africa. Cryptococcal meningitis is a metric of HIV treatment programme failure; timely HIV testing and rapid linkage to care remain an urgent priority. Funding: None.